Effect of training day, match, and length of the microcycle on the worst-case scenarios in professional soccer players - Oliva-Lozano, J. M.; Gómez-Carmona, C. D.; Rojas-Valverde, D.; Fortes, V.; Pino-Ortega, J. (Research in Sports Medicine, 2021)
This study aimed to describe in-season worst-case scenarios (WCS) of professional soccer players and compare the WCS between training and match days (MD), considering the length of microcycle. A cohort study was designed for four competitive mesocycles in LaLiga123. The WCS of distance covered (DIS), high-speed running distance (HSRD), and sprinting distance (SPD) for four different WCS durations (1', 3', 5', 10') were analysed. Statistical differences between the WCS from training and MD were found at all intensities and periods. The magnitude of differences was moderate in DIS-1' (F=15.49; p<0.01; ?p2=0.09) and DIS-3' (F=20.99; p<0.01; ?p2=0.12), and high in the rest of variables (F=26.53-89.41; p<0.01; ?p2=0.15-0.38). Specifically, the WCS from MD reported the highest values at all intensities and periods. Regarding training days, the greatest WCS of DIS, HSRD, and SPD were found on MD-4, MD-3, and MD+1. Considering the length of microcycle, significant differences (p<0.05) in training-days' WCS,but notin MD (p>0.05). In conclusion, specific WCS training programmes (e.g., including 1 min to 10-min training drills in MD-4) may be useful to prepare the demands required on MD.